Issues of the contemporary in Tsai Ming-liang: Memory, distancing, and sexuality - Felipe, Marcos Aurélio (2018)
We approach the cinema as a problematizing narrative of the contemporaneity, from the memory, affective distancing, and sexuality, which are decisive for artistic-cultural representations. We analyzed the movie Goodbye, Dragon Inn (2003, by Tsai Ming-liang) from a comparative and filmographic perspective with contemporary Asian cinema. We understand that a movie belongs to a tradition and dialogues with the cinema of its time.  Film analysis should seek a greater understanding of the significance operations, sensory, and historical-cultural components of films. In this way, we start from the perspectives that contemplate contemporaneity and the language of cinema. We note that the work of Tsai Ming-liang is hand in hand with the contemporary and develops constant narratives and a fine reflection on itself, its means, and aesthetic potential.